Al-Taubat Dalam Perspektif Hadits Nabi - Canra Krisna Jaya (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
This article aims to explain how repentance is a form of confession of a servant for the mistakes he has made, seen from the perspective of the Hadith of the Prophet Muhammad. This study uses a type of literature study with a qualitative approach. The primary data used are several main books of Hadith, then several books of Hadith Syarah. This article concludes that the teaching of repentance has consequences as well as implications for one's life. When repentance is understood in depth, it will be able to encourage someone to create a more positive life vision and mission. This is because an absolute truth or truth is only in the hands of God, so any falsehood should be returned to God as soon as possible in order to get the truth back. The truth and goodness that a person perceives are relative and relative, so he must be willing to have a dialogue about the truth by living it with steadfastness and not knowing stopping. Thus, repentance should not only be seen as a religious commandment, because in a deeper review, it turns out that it is able to guide a person to live a more wise, positive and constructive life.